DEMOCRACY AND EMPLOYMENT RELATIONSHIP: CORPORATE SOCIAL RESPONSIBILITY - Oliveira, Paulo Eduardo Vieira de (Revista Direitos Culturais, 2020)
Within the thematic of the application of the democracy under the political, economic, social and cultural slopes, there is the development of the same within the labor sphere. The concepts of democracy, employment relationship and social responsibility of the company, although at first seem disconnected, intertwine when one sees the applicability of democracy within the company. A State to be effectively democratic in law, there must be the application of democracy under various spheres, including labor. Thus, this article seeks, through a bibliographical review, to present the concepts of democracy and social responsibility of the company, demonstrating the applicability of the same in the relation employee x employer, presenting answers about the proposed questioning.